Gaming-value and culture-value: Understanding how players account for video game purchases. (December 2019) - Johnson, Mark R; Luo, Yinyi
In most writing on video games, whether within or beyond the academy, the availability of gaming media is implicitly taken for granted. However, we propose that the act of video game purchase should be seen as an important aspect of the player–video game relationship. Drawing on original interview data, this work explores two types of video game purchasing that are common in contemporary Western gaming culture – the 'pre-order' (paying for a game before its release), and what we term 'backlog purchasing' (buying a cheap game unlikely to ever be played). Through Marx and Adorno's theorizations of value, specifically exchange-value and use-value, we argue that, according to players, the meaningful aspects of those purchases are more than simply obtaining the entertainment value realized through gaming. Instead, different kinds of purchases activities are themselves imbued with varied and powerful values, by both players and the industry. We call these 'gaming-value' and 'culture-value'. Furthermore, drawing on Lewis' conceptualization of consumer capitalism, this article also traces the ideological root of, and the flow of power beneath, these two particular types of consumption. Through analysing video game purchases, we aim to shed light upon a crucial element of the audience–media relationship, as well as other theoretical issues, most notably adapting and updating Marxist concepts for the purpose of researching modern video games.